Activation of MMP‐9 by membrane type‐1 MMP/MMP‐2 axis stimulates tumor metastasis. Issue 3 (16th March 2017) - Li, Zichen; Takino, Takahisa; Endo, Yoshio; Sato, Hiroshi
Abstract : An artificial receptor for proMMP‐9 was created by fusing tissue inhibitor of MMP‐1 (TIMP‐1) with type II transmembrane mosaic serine protease (MSP‐T1). Expression of MSP‐T1 in 293T cells induced binding of proMMP‐9, which was processed by MMP‐2 activated by membrane type 1 MMP (MT1‐MMP). HT1080 cells transfected with the MSP‐T1 gene produced activated MMP‐9 in collagen gel, and addition of proMMP‐2 to the culture augmented it, which resulted in intensive collagen digestion. These cells metastasized into chick embryonic liver more than control cells. Treatment of HT1080 cells with concanavalin A in the presence of exogenous proMMP‐2 induced activation of not only proMMP‐2 but also proMMP‐9. Knockdown of MT1‐MMP or TIMP‐2 expression with siRNA suppressed activation of both proMMP‐2 and proMMP‐9. Transfection of TIMP‐1 siRNA suppressed cell binding and activation of proMMP‐9, but not proMMP‐2 activation. Knockdown of a disintegrin and metalloproteinase 10 (ADAM10) expression reduced cell binding and processing of proMMP‐9. These results suggest that proMMP‐9, which binds to a receptor complex containing TIMP‐1 and ADAM10, is activated by the MT1‐MMP/MMP‐2 axis, and MMP‐9 thus activated stimulates cellular proteolysis and metastasis. Abstract : ProMMP‐9 which binds to a receptor complex containing TIMP‐1 and ADAM10 is activated by MT1‐MMP/MMP‐2 axis. MMP‐9 thus activated stimulates cellular proteolysis and metastasis.